2022
DOI: 10.1111/ane.13698
|View full text |Cite
|
Sign up to set email alerts
|

Blood biomarkers in ALS : challenges, applications and novel frontiers

Abstract: Amyotrophic lateral sclerosis (ALS) is the most common motor neuron disease among adults. With diagnosis reached relatively late into the disease process, extensive motor cell loss narrows the window for therapeutic opportunities. Clinical heterogeneity in ALS and the lack of disease‐specific biomarkers have so far led to large‐sized clinical trials with long follow‐up needed to define clinical outcomes. In advanced ALS patients, there is presently limited scope to use imaging or invasive cerebrospinal fluid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 124 publications
2
23
0
1
Order By: Relevance
“…We measured mitochondrial antioxidant activity in platelets obtained from peripheral blood since this was easily accessible and was a source of biomarkers for neuroaxonal and muscle degeneration. It may therefore be more representative of ALS pathobiology than samples extracted from other sources [40]. We also observed that this decrease in Aco2 activity was independent of our patients' respiratory, nutritional and functional status.…”
Section: Discussionsupporting
confidence: 51%
“…We measured mitochondrial antioxidant activity in platelets obtained from peripheral blood since this was easily accessible and was a source of biomarkers for neuroaxonal and muscle degeneration. It may therefore be more representative of ALS pathobiology than samples extracted from other sources [40]. We also observed that this decrease in Aco2 activity was independent of our patients' respiratory, nutritional and functional status.…”
Section: Discussionsupporting
confidence: 51%
“…Biomarkers of Alzheimer’s disease (AD) pathophysiology, namely amyloid-beta, phospho-tau (p-tau) and total tau (t-tau), and those detecting neuroaxonal degeneration, as neurofilament light chain (NfL), have provided the most substantial impact 5 6. Moreover, reliable assays that can detect p-tau and NfL in blood have become available, paving the way for more widespread use of these biomarkers in clinical practice 7 8. In particular, the measurement of blood p-tau is increasingly considered a realistic, cost-effective and non-invasive assay that will help the diagnostic process for patients with cognitive decline 7 9 10.…”
Section: Introductionmentioning
confidence: 99%
“…Factors that compromise the utility of blood include the presence of high abundance proteins (e.g., albumin) that interfere with the detection of low concentration proteins, sequestration in different aggregates and the formation of immunocomplexes or changes in molecular processes due to the pathophysiology of the disease (e.g., clearance of misfolded proteins by chaperones). A more detailed description of these features is beyond the scope of this review, but we recommend the work of Sturmey et al [ 13 ] for a more comprehensive discussion.…”
Section: Fluid-based Biomarkers In Als: the Importance Of The Study S...mentioning
confidence: 99%